Distribution of ABO and Rhesus Blood Group in Healthy Population of District Hyderabad, Sindh - Shaikh, Shakil Ahmed; Laghari, Zulfiqar Ali; Memon, Salma Farukh; Warsi, Jamshed (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To establish the trends of ABO and Rh (Rhesus) Blood group in district Hyderabad, Sindh. Methodology: This cross-sectional study carried out at department of Physiology University of Sindh Jamshoro from August-December 2019. Simple random technique used for collection of data. In this study, 4000 participants included to establish the trends of ABO and Rh blood group by standard method. Consent taken from all participants, after they have been informed about this study. Data analyzed on SPSS 16.0 version software. Results: The most common blood group found was B (35%), followed by O (33.25%), A (22.25%) and less common blood group is AB (9.5%). The majority of population is Rh-positive 92%, where as 8% is Rh-negative. Conclusion: Incidence of B blood group is higher than O,A, and AB and incidence of Rhesus positive is common against Rhesus negative. Keywords: ABO Blood Group, Rhesus Blood Group, Incidence.